Course Design in Competency-Based Education: An Approach Based on ADDIE - Williams, Kevin (Competency-Based Education Research Journal, 2025)
Competency-Based Education (CBE) is transforming current teaching and learning through prioritizing skill mastery over traditional time-based instruction. This shift in teaching and learning attempts to ensure graduates are job-ready and aligned with industry demands. However, many institutions and instructors face challenges in designing effective CBE programs due to a lack of structured instructional design frameworks. This paper proposes the CBE-ADDIE Model, which integrates the well-established ADDIE framework with CBE principles. The newly developed model provides a more robust and systematic approach for competency mapping, assessment design, content development, implementation, and continuous evaluation. By adopting this model, instructional designers and educators can create high-quality, scalable, and industry-aligned CBE programs that enhance learner success and workforce readiness.